2011
DOI: 10.1039/c0jm04587j
|View full text |Cite
|
Sign up to set email alerts
|

Formation, morphology control and applications of anodic TiO2 nanotube arrays

Abstract: Anodic titanium dioxide films, especially anodic TiO 2 nanotube arrays, have attracted extensive interest in the past decade. A number of electrolytes, either aqueous or non-aqueous, fluoride containing or fluoride free, have been chosen to grow anodic titanium oxide films. With great improvements in the morphology control on porosity, pore size, nanotube length and pore ordering, anodic titanium oxide films have been widely applied in photochemical water splitting, hydrogen sensing, dye-sensitized solar cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
160
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 170 publications
(208 reference statements)
2
160
0
2
Order By: Relevance
“…[1][2][3] Recently, it has been demonstrated that ordered arrays of crystalline titania nanotubes (NTs) exhibit enhanced photocatalytic properties as compared to other titania morphologies, largely attributed to their high surface area. 4,5 This functionality is greatly affected by the crystallographic structure, surface bonding character, particle size, morphology and the electronic structure. In addition, there is a potential positive correlation between the magnetic structure and photocatalytic behavior in this system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, it has been demonstrated that ordered arrays of crystalline titania nanotubes (NTs) exhibit enhanced photocatalytic properties as compared to other titania morphologies, largely attributed to their high surface area. 4,5 This functionality is greatly affected by the crystallographic structure, surface bonding character, particle size, morphology and the electronic structure. In addition, there is a potential positive correlation between the magnetic structure and photocatalytic behavior in this system.…”
Section: Introductionmentioning
confidence: 99%
“…Among these processes, the electrochemical anodization of titanium in fluorinated electrolytes is a simple method to synthesize porous highly vertically ordered structures with high aspect ratios. The process of self organization of nanotube is a complex mechanism [10]- [13] and requires extensive study. The properties of self-organized TNA can be tailored using various anodization conditions and post deposition treatment.…”
Section: Introductionmentioning
confidence: 99%
“…14,18-21 Just as Zhou et al 20 indicated, both the field-assisted dissolution and the 'plastic flow' models cannot explain the formation of gaps and ribs around the nanotubes.…”
mentioning
confidence: 99%
“…[8][9][10] However, ATNTs have been achieved in an aqueous H 2 SO 4 solution as well as other fluoride free solutions. [19][20][21] This fact puts the fluoride effect ([TiF 6 ] 2− ) and the field-assisted dissolution into question. 20 So far, the driving forces of the 'plastic flow' and field-assisted dissolution are still controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation